Chewing as a forming application: A viscoplastic damage law in modelling food oral breakdown - Skamniotis, CG; Charalambides, MN; Elliott, M (AIP Publishing, 2017)
The first bite mechanical response of a food item resembles compressive forming processes, where a tool is pressed into a workpiece. The present study addresses ongoing interests in the deformations and damage of food products, particularly during the first bite, in relation to their mechanical properties. Uniaxial tension, compression and shear tests on a starch based food reveal stress-strain response and fracture strains strongly dependent on strain rate and stress triaxiality, while damage mechanisms are identified in the form of stress softening. A pressure dependent viscoplastic constitutive law reproduces the behavior with the aid of ABAQUS subroutines, while a ductile damage initiation and evolution framework based on fracture toughness data enables accurate predictions of the product breakdown. The material model is implemented in a Finite Element (FE) chewing model based on digital pet teeth geometry where the first bite of molar teeth against a food item is simulated. The FE force displacement results match the experimental data obtained by a physical replicate of the bite model, lending weight to the approach as a powerful tool in understanding of food breakdown and product development.